Postglacial changes in El Nino and La Nina behavior - Makou, Matthew C.; Eglinton, Timothy I.; Oppo, Delia W.; Hughen, Konrad A. (Geology, 2010)
Paleoclimate reconstructions suggest distinctive changes in the Ell Nino-Southern Oscillation (ENSO), the dominant mode of tropical climate variability, over the last glacial cycle and throughout the Holocene. However, to the best of our knowledge, no studies provide parallel reconstructions of warm (El Nino) and cold (La Nina) phase variability, thus precluding distinction between variations in ENSO activity and the mean state of the tropical Pacific. Here we provide the first such records, generated using molecular organic geochemical proxies in a sediment core from the Peru margin region. The opposing influences of El Nino and La Nina on coastal upwelling and phytoplankton community structure produce distinct sedimentary sterol records describing the evolution of each ENSO phase. We document changes in surface ocean productivity on the Peru margin over the past 16 ka that indicate enhanced La Nina-like conditions alone during deglaciation, but concomitant increases in both El Nino and La Nina activity during the past 2 ka. We propose that the preponderance of La Nina-like conditions prior to 11.5 ka reflects the influence of waning glacial boundary conditions. By contrast, warm and cold phase covariability during the late Holocene suggests centennial-scale changes in ENSO activity, rather than the Pacific mean state, driven by tropical insolation.
id: 1985; PT: J; UT: WOS:000273346200011